Fostering Religious Values in Early Childhood Through Big Book Media at TK Negeri 5 Banda Aceh - Hanum, Rafidhah; Irwandi, Irwandi; Azila, Silvia (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
Instilling religious and moral values in early childhood is both crucial and challenging, especially in culturally and religiously rich contexts like Aceh, Indonesia. Many early childhood education centers still rely on traditional teaching methods that are less engaging for young learners. This study addresses the need for innovative, context-sensitive media by developing and evaluating a big book designed to foster courtesy, gratitude, and respect among children at TK Negeri 5 Banda Aceh. The research followed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Experts in early childhood Islamic education and educational media validated the content and design. The big book was then implemented with ten children aged 5–6 in classroom sessions, with behavioral changes observed through checklists and qualitative feedback from teachers and students. Expert validation confirmed the big book’s feasibility and relevance, with scores of 71.8% (content expert) and 86.5% (media expert). Classroom trials showed a marked increase in children’s spontaneous use of polite language, expressions of gratitude, and respectful behaviors. The overall group achievement reached 90% on behavioral indicators, and both teacher and student feedback highlighted the book’s appeal and positive influence on daily interactions. This study demonstrates that well-designed big book media can make values education tangible and enjoyable for young children. While the findings are limited to one school and a small sample, they offer practical insights for educators and policymakers interested in strengthening character education through engaging, culturally grounded storytelling. Further research with larger and more diverse groups is recommended to explore the long-term effects and wider applicability of this approach.